Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1080/02770903.2018.1534967
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and disease burden of severe eosinophilic asthma in Japan

Abstract: Background: There are limited data on the prevalence and burden of severe eosinophilic asthma (SEA) both in Japan and globally. This study aimed to assess the prevalence and burden of SEA in Japan. Methods: This study was a retrospective, observational cohort analysis using health records or health insurance claims from patients with severe asthma treated at Kyoto University Hospital. The primary outcome was the prevalence of SEA, defined as a baseline blood eosinophil count !300 cells/lL. Secondary outcomes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 29 publications
(42 reference statements)
6
16
0
Order By: Relevance
“…17,18 In several studies, including TENOR (Epidemiology and Natural History of Asthma: Outcomes and Treatment Regimens), patients experiencing a recent exacerbation were 6-to 8-fold more likely to experience a future exacerbation than those without a recent exacerbation. 13,19,20 Consistent with this finding, the present study's multivariate analysis showed that the risk of exacerbations during the follow-up period increased in patients who currently had severe asthma or eosinophilic disease or who had experienced asthma exacerbations in the previous year. Among patients with severe asthma, the risk of a subsequent exacerbation increased in patients who experienced an exacerbation in the previous year and in patients who used daily oral corticosteroids for 3 months.…”
Section: Decreased Risk Increased Risksupporting
confidence: 87%
See 1 more Smart Citation
“…17,18 In several studies, including TENOR (Epidemiology and Natural History of Asthma: Outcomes and Treatment Regimens), patients experiencing a recent exacerbation were 6-to 8-fold more likely to experience a future exacerbation than those without a recent exacerbation. 13,19,20 Consistent with this finding, the present study's multivariate analysis showed that the risk of exacerbations during the follow-up period increased in patients who currently had severe asthma or eosinophilic disease or who had experienced asthma exacerbations in the previous year. Among patients with severe asthma, the risk of a subsequent exacerbation increased in patients who experienced an exacerbation in the previous year and in patients who used daily oral corticosteroids for 3 months.…”
Section: Decreased Risk Increased Risksupporting
confidence: 87%
“…8e11 A cross-sectional survey conducted in northern California found that the total per-person costs for severe asthma are almost triple those for moderate asthma. 9 In Japan, although several studies 12,13 have been conducted to assess severe asthma subphenotypes in patients treated in a hospital-based setting, the clinical characteristics, disease burden, and patient behavior have not been well documented for severe asthma treated in various clinical settings, including local hospitals and clinics.…”
Section: Introductionmentioning
confidence: 99%
“…We also found that for Japanese patients with severe asthma, asthma-associated total outpatient costs and hospitalization costs (per patient) increased with age. The total outpatient cost associated with severe asthma (¥319,436/patient/year) was similar to that previously reported by Nagasaki et al (¥357,958/patient/year) [14]. Since Nagasaki et al [14] estimated medical costs between 2013 and 2014 using claims data in Kyoto University Hospital, the characteristics of the study population might have been similar to those in our study.…”
Section: Discussionsupporting
confidence: 90%
“…The total outpatient cost associated with severe asthma (¥319,436/patient/year) was similar to that previously reported by Nagasaki et al (¥357,958/patient/year) [14]. Since Nagasaki et al [14] estimated medical costs between 2013 and 2014 using claims data in Kyoto University Hospital, the characteristics of the study population might have been similar to those in our study. However, another retrospective cohort study conducted by Inoue et al reported the total outpatient cost (comprising ER visits, outpatient visits, and prescriptions) of ¥141,515/patient/year between 2009 and 2015; this discrepancy may be due to the study period.…”
Section: Discussionsupporting
confidence: 90%
“…Sixteen cohort studies, [10][11][12][13][14][15][16]18,19,21,28,[36][37][38][39][40] 6 cross-sectional studies, 7,8,20,25,41,42 and one case-control study 17 examined the association of elevated blood eosinophil count with asthma exacerbation.…”
Section: Asthma Exacerbationmentioning
confidence: 99%